Power imbalance, bullying and harassment in academia and the glocal (local and global) workplace - Patel, Fay (Bullying and victimization., 2021)
"The book Power Imbalance, Bullying and Harassment in Academia and the Glocal (Local and Global) Workplace introduces a candid and open discussion on a sensitive topic. Breaking the "code of silence" on bullying and harassment (including sexual harassment) in academia and the glocal workplace is the central focus of the book. The author advocates a call to action to hold perpetrators and the executive leadership teams of higher education institutions and corporate organizations accountable and responsible for bullying and harassment behaviors in the glocal (local and global) workplace. The book aims to raise the bar for ethical considerations in working with employees who may be vulnerable in the glocal workplace; to call out the perpetrators of bullying and harassment in the glocal workplace and academia; to ensure that the mental wellbeing of employees is a priority; to place responsibility and accountability for bullying and harassment on the shoulders of the executive leadership of international higher education institutions and corporations; and to call upon stakeholder groups to shatter the "code of silence" with a youtoobullyharrasser movement. Employers are expected to enhance their vigilance on the matter of bullying and harassment and to report perpetrators through a national and international monitoring system which names the perpetrators and prevents them from causing harm in their current organization and from moving surreptitiously to other workplace communities. This book is an account of bullying and harassment in academia and other workplaces written by those who experienced and/or witnessed bullying and harassment. It includes chapters on the political economic factors influencing equity, diversity and inclusion agendas over decades; the impact of bullying and harassment in the COVID-19 period when various communities are vulnerable; and critically reviews and presents real-life scenarios in academia and the glocal workplace which are both covert and overt. However, these underhanded activities, often with the knowledge and approval of executive leadership, remain unchallenged by employees and stakeholder groups because of the threat of loss of one's livelihood. The contributors bring valuable insights into the covert operations of the perpetrators, who are sometimes the executive leaders (women and men) themselves. This book is essential for understanding the dark web of deceit, lies, conspiracies and mobbing cultures which ensnares innocent targets, across glocal organizational contexts. Profiles and descriptors within the chapters and case studies act as alert signals to identify bullies. The contributors bring personal, creative and academic perspectives together, offering the readership sobering and authentic accounts of traumatic experiences and challenges in the glocal workplace"--